2015
DOI: 10.1037/ort0000018
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for suicidal behaviors among Filipino Americans: A data mining approach.

Abstract: Filipino Americans have lower suicide rates than other Asian ethnic groups. The present study examined risk factors for suicide ideation and attempt among Filipino Americans with random forest. The data were from the Filipino American Community Epidemiological Study (Takeuchi, 2011). The results showed that the important predictors for suicide ideation were depressive disorder, substance use disorder, and years in the United States. The important predictors for suicide attempt were the number of family relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 40 publications
1
41
0
Order By: Relevance
“…David, Sharma, and Petalio (2017) identified that Filipinos not only are collectivistic but also possess the unique indigenous Filipino core value kapwa (i.e., a worldview in which the self is not distinguished from others; Enriquez, 1994). Researchers also note how social support is a protective factor against mental health issues among Filipino Americans (e.g., Kuroki, 2015; Sanchez & Gaw, 2007; Tsai & Thompson, 2013). For example, low social support was associated with mental health problems and substance use among Filipino immigrant workers (Tsai & Thompson, 2013).…”
Section: Mental Health Help‐seeking Of Filipino Americansmentioning
confidence: 99%
See 1 more Smart Citation
“…David, Sharma, and Petalio (2017) identified that Filipinos not only are collectivistic but also possess the unique indigenous Filipino core value kapwa (i.e., a worldview in which the self is not distinguished from others; Enriquez, 1994). Researchers also note how social support is a protective factor against mental health issues among Filipino Americans (e.g., Kuroki, 2015; Sanchez & Gaw, 2007; Tsai & Thompson, 2013). For example, low social support was associated with mental health problems and substance use among Filipino immigrant workers (Tsai & Thompson, 2013).…”
Section: Mental Health Help‐seeking Of Filipino Americansmentioning
confidence: 99%
“…For example, low social support was associated with mental health problems and substance use among Filipino immigrant workers (Tsai & Thompson, 2013). Additionally, Kuroki (2015) found that social connectedness is a protective factor against suicide among Filipino Americans. However, there are no studies exploring the relationship between Filipino Americans’ social support and their mental health help‐seeking behavior.…”
Section: Mental Health Help‐seeking Of Filipino Americansmentioning
confidence: 99%
“…In another study, Kessler and colleagues [ 40 ] predicted suicide in a sample of soldiers and veterans and found male sex, criminal offenses, and previous suicide ideation as the most influential risk factors for completed suicide. Kuroki [ 41 ] used a data mining approach to predict suicidal behaviors among 624 Filipino Americans and found depression and substance use disorder as the critical predictors of suicidal ideation. This study, however, did not focus on the sensitivity and specificity of the proposed diagnosis system.…”
Section: Introductionmentioning
confidence: 99%
“…For the analysis, yes was coded as “1” and, no was coded as “0.” These questions were widely used in previous studies. [ 10 , 25 , 32 ]…”
Section: Methodsmentioning
confidence: 99%
“…[ 6 , 7 ] In particular, depression was the most proximal and the strongest predictor of adult suicide in many studies. [ 8 10 ]…”
Section: Introductionmentioning
confidence: 99%